Grounding Green Pesantren: Revitalization of Pesantren-Based Ecological Scientific - Mufid, Moh. (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2019)
This article aims to examine the role of schools in fostering an attitude of eco-literacy students and ensuring environmental sustainability by green lifestyle implementation (green lifestyle). The idea of green schools is an attempt to realize the millennial generation of environment-friendly students. To support this, it needs revitalization ecologically sound scientific schools: First, revitalization in the field of interpretation studies with an ecological approach. Second, the revitalization of jurisprudence with ecological insights. Third, develop an ecological study of Sufism. The results show that Islamic boarding schools as educational institutions have great potential to solve social problems ecologically. Pesantren can be a model of education that instils the normative ecological-religious value to foster self-consciousness and care about the environment. Therefore, it takes a revitalization of knowledge in pesantren to give birth to piety and ecological awareness among the students. Revitalization of knowledge in pesantren can be done through the internalization of ecological insight into the discipline of the religious sciences that are taught in schools. Study commentary directed at understanding the verses with a thematic-ecological approach that can provide insight into the Qur’an in a comprehensive manner to the students to interact with their environment. Jurisprudence oriented towards environmental issues that can be equipped to respond to the dynamics of Islamic legal thought that is responsive to the problems of social-ecological. Likewise, the study of Sufism is done by the redefinition of the terms of the key disciplines of Sufism, like repentance, asceticism, mahabbah, and others, thus produce an environmental ethics attitude.